(untitled) (Research, Society and Development, 2022)
The activities of health professionals foresee the constant contact and handling of chemical agents. Therefore, knowledge about chemical risk is essential for personal safety both in the work environment and in the teaching environment. This research aimed to understand the perception of students in the health area about the risks related to the presence of chemicals in their study and/or work environment. This is a descriptive study with a quantitative approach, carried out in a private institution of Higher Education (HEI) in the city of Brasília (Brazil), with students from biomedicine, biological sciences and nursing, with the application of a questionnaire. Results showed that students are more concerned with social issues such as pedophilia or racial intolerance than those related to the presence of chemicals. Most students mentioned cancer as an issue of concern, but the absence of risk perception is observed in issues considered to be of little concern, such as cigarette use. Regarding the hazardous nature of chemicals and professional activities, vaccination, antibiotics, blood tests, ethyl alcohol and iodine were considered as non-hazardous. Although these may also present risks to professional health, the results showed that the students did not perceive them as risks. The obtained data indicate that most students have a low level of risk perception in the presence of chemicals, and it is suggested that questions about toxicology and biosafety should be intensified during the academic training process.